2021
DOI: 10.3390/pharmaceutics13020260
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Morphological and Release Profiles in Ocular Implants of Acetazolamide Prepared by Electrospinning

Abstract: The visual impairment that often leads to blindness causes a higher morbidity rate. The goal of this work is to create a novel biodegradable polymeric implant obtained from coaxial fibers containing the dispersed drug—acetazolamide—in order to achieve sustained drug release and increase patient compliance, which is of the highest importance. Firstly, during this work, uncoated implants were produced by electrospinning, and rolled in the shape of small cylinders that were composed of uniaxial and coaxial fibers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Recent DDS studies propose the use of electrospinning biodegradable polymers that are more adaptable and rapidly dissolve in the cornea due to their highly porous structure. Andreadis et al (2022) created an in situ electrospun film gel for the delivery of timolol maleate [ 96 ], and similarly, Morais et al (2021) developed electrospun ocular implants for acetazolamide delivery [ 97 ]. Both showed a significant sustained IOP-lowering effect and increased local delivery.…”
Section: Nano-based Dds For Glaucomamentioning
confidence: 99%
“…Recent DDS studies propose the use of electrospinning biodegradable polymers that are more adaptable and rapidly dissolve in the cornea due to their highly porous structure. Andreadis et al (2022) created an in situ electrospun film gel for the delivery of timolol maleate [ 96 ], and similarly, Morais et al (2021) developed electrospun ocular implants for acetazolamide delivery [ 97 ]. Both showed a significant sustained IOP-lowering effect and increased local delivery.…”
Section: Nano-based Dds For Glaucomamentioning
confidence: 99%
“…As a norm, the core flow rate should always be smaller than the shell flow rate, so a complete coverage of the core can be attained and continuous fibers can be formed [22]. Morais et al showed exactly that by generating core-shell fibers with smooth surfaces without irregularities, which indicates that the implant coating surface has an extensive pore network and tubules that completely cover the inner region for a sustainable release of the entrapped drug [79].…”
Section: Core-shellmentioning
confidence: 99%
“…The ES process has also found to be advantageous in developing fibrous mats for novel controlled drug delivery systems via an array of administration routes such as buccal [59,371,372], nasal [373][374][375], transdermal [194,376,377] and ocular [378][379][380][381][382]. ES has found to have the ability to overcome limitations of conventional drug delivery routes of administrations e.g.…”
Section: Electrospinningmentioning
confidence: 99%
“…The resulting fibrous coatings showed an increase in drug release; up to 20% more timolol maleate was released from the coatings compared to permeation enhancer-free coatings. More recently, coaxial fibers containing acetazolamide were fabricated to create a novel biodegradable polymeric ocular implant [378]. The PCL based implants exhibited sustained release of the drug following coating of poly (ethylene-co-vinyl acetate), engineering an innovative implant advantageous over existing ocular drug delivery systems.…”
Section: Electrospinningmentioning
confidence: 99%